Towards a typology of personal information management behavior: exploring and defining people's interactions with personal information. Issue 6 (7th October 2020) - Alon, Lilach; Forkosh Baruch, Alona; Nachmias, Rafi
Abstract : Purpose: Differences in personal information management (PIM) behavior are well established in the literature, but are defined from the narrow perspective of practical use (e.g. filing/piling, emailing). This paper aims to identify the types of PIM behavior that would help us understand how people manage personal information in the digital era. Design/methodology/approach: The authors relied on the theoretical framework, published in a recent article (Alon and Nachmias, 2020a), examining actual PIM behavior (e.g. actual practice), ideal behavior (e.g. perceptions of best practice) and the gaps between them. Our framework drew on data collected via a questionnaire on the use of 25 PIM practices ( N = 465). Findings: The findings indicated four types of PIM behavior that differed by activity level (actual PIM) and satisfaction level (ideal PIM and gaps): passive and satisfied, active and satisfied, fairly active and unsatisfied and active and fairly satisfied. This allows the classification of users according to their dominant tendency to use specific practices. Originality/value: Previous studies focused mainly on specific PIM practices or contexts. Our research creates a classification of types, based on ideal as well as actual PIM behavior, and also examines a broader perspective.